UJI EFEKTIVITAS ANTIOKSIDANT (IC50) DAN TOKSISITAS AKUT (LD50) FRAKSI ETANOL DAUN NANGKA (Artocarpus Heterophyllus Lam.) - Recta Olivia Umboro; Dedent Eka Bimmaharyanto S; Ni Komang Wijiani Yanti (Lembaga Penelitian dan Pendidikan Mandala, 2020)
Antioxidants are needed by the body to ward of free radicals from internal and external factors. The presence of free radicals is related to human helath conditions. Back to nature lifestyle and the high cost of drugs therapy makes people preferring to use traditional medicine. Jackfruit (Artocarpus heterophyllus Lam) leaves is contain several secondary metabolites such a flavanoids, alkaloids, sapaonins, steroids and tannins. Flavanoid have an antioxidant effect.In this study, the antioxidant activity of ethanol jackfruit (Artocarpus heterophyllus Lam) leaves extract was tested using 1,1-diphenyl-2-picrylhidrazyl (DPPH) method by UV-Vis Spectrophotometry, wich Vitamin C as comparison standart. Acute toxicity test was carried out by giving oral doses of ethanol jackfruit leaf extract to 4 groups of male rats. Group I as a control (aquadest);II(100mg/30gBW);III (150mg/30gBW); IV (200mg/30gBW) were then observed for 7 days.The antioxidant activity test showed that ethanol jackfruit (Artocarpus heterophyllus Lam) leaves extract had effectiveness as an antioxidant with an IC50 value of 58.58 ppm. The data were analyzed using one-way ANOVA showing sig value 0.228, which means (P>0.005), then followed by post hoc test, an average value of 0.00,probability value is 1.000 (sig>0.005). It can be concluded that there is no significant difference between the control and the treatment dose of 100mg, and there is a significant difference in the 150mg/30gBW, 200mg/30gBW dose groups. LD50 value dosage range in 150mg and 200mg.